2019
DOI: 10.3892/mmr.2019.10904
|View full text |Cite
|
Sign up to set email alerts
|

Partial hepatectomy‑induced upregulation of SNHG12 promotes hepatocyte proliferation and liver regeneration

Abstract: Following partial hepatectomy (pH), the complex process of liver regeneration is initiated, which encompasses the synchronized induction of hepatocyte proliferation. Hepatocyte proliferation can be regulated by multiple stimuli, including long non-coding rnas (lncrnas) and Wnt/β-catenin signaling, although the underlying mechanism of lncrna/Wnt in liver regeneration remains unclear. in the present study, a liver regeneration-associated functional lncrna was identified, and its function was delineated in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Before cell transplantation for the treatment of inherited metabolic liver diseases, the host liver is often pre-treated to increase cell engraftment in vivo using a variety of strategies, such as partial hepatectomy, portal ligature/ embolization, or administration of chemotherapeutic drugs, which provide necessary stimuli for preparation of donor cell housing. [149][150][151][152] For instance, Pourcher et al 152 showed that cell engraftment was increased by around 3-folds after inducing volumetric portal embolization in the C57BL6 mice using polyester microspheres and subsequently injection of hepatocytes into the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Before cell transplantation for the treatment of inherited metabolic liver diseases, the host liver is often pre-treated to increase cell engraftment in vivo using a variety of strategies, such as partial hepatectomy, portal ligature/ embolization, or administration of chemotherapeutic drugs, which provide necessary stimuli for preparation of donor cell housing. [149][150][151][152] For instance, Pourcher et al 152 showed that cell engraftment was increased by around 3-folds after inducing volumetric portal embolization in the C57BL6 mice using polyester microspheres and subsequently injection of hepatocytes into the spleen.…”
Section: Discussionmentioning
confidence: 99%
“… 108 , 109 , 110 Other studies have also demonstrated that certain genes act as the regulators of Wnt/β-catenin pathway, which accelerates hepatocyte growth and LR by regulating Wnt/β-catenin pathway. 111 , 112 Yin and Clemens et al. proved that Wnt/β-catenin pathway had a crucial effect on the initiation stage of LR from the opposite side, and reducing glycogen synthase kinase-3β (GSK-3β) phosphorylation affected the Wnt/β-catenin pathway, thereby inhibiting LR.…”
Section: Signaling Pathways In Lrmentioning
confidence: 99%
“…42,43 In mice receiving PHx, SNHG12 overexpression significantly increased PCNA-positive hepatocytes by stimulating Wnt/β-catenin signaling, whereas the liver regeneration promoted by SNHG overexpression was alleviated by Wnt inhibitor IWR-1. 44 Inhibition of factors that interfere with the cell cycle can also boost liver regeneration. As a cell cycle halter, p21 suppressed cell cycle progression in hepatocytes and impeded liver regeneration.…”
Section: Stimulating Proliferation During Liver Regenerationmentioning
confidence: 99%